The role of LoBALs in quasar evolution. Issue Volume 15:Issue S356(2019) (October 2019) - Wethers, Clare; Kotilainen, Jari; Schramm, Malte; Schulze, Andreas
Abstract: Broad absorption line quasars (BALs) represent an interesting yet poorly understood population of quasars showing direct evidence for feedback processes via powerful outflows. Whilst an orientation model appears sufficient in explaining the sub-population of high-ionisation BALs (HiBALs), low-ionisation BALs (LoBALs) may instead represent an evolutionary phase, in which LoBALs exist in a short-lived phase following a merger-driven starburst. Throughout this work, we test this evolutionary picture of LoBALs by comparing the FIR detection rates, SFRs and environments for a sample of 12 LoBALs to other quasar populations at 2.0 < z < 2.5, making use of archival Herschel SPIRE data. We find the LoBAL detection rate to exceed that of both HiBALs and non-BALs, indicating a potential enhancement in their SFRs. Indeed, we also find direct evidence for high SFRs (>750 Mȯ yr −1 ) within our sample which may be consistent with an evolutionary paradigm.